Modeling and visualizing competitiveness in soccer leagues - Lopes, António M. (2021)
This paper adopts concepts of systems’ theory and multidimensional scaling to study the competitiveness in soccer leagues of four countries. A season for a given league is read as a dynamical system with states that are measured at discrete time samples corresponding to the rounds. The system state is inferred from the accumulated points won and lost by each team. These data series are interpreted as active and reactive power and are processed in the complex plane. The league competitiveness is visualized through 2-dim maps of items that represent the relative positioning of the teams over the season. The results are compared with those obtained with two classic competitiveness measures.